Influences of Restaurant Servicescape and Services Quality on Repurchase Intention through Customer Satisfaction in Semarang - Steven Pradipta Kundiarto; Sentot Suciarto (Soegijapranata Catholic University, 2022)
Every restaurant must find a way to attract new customers and retain the existing ones to create repurchase intention. This study aims to determine customer repurchase intention in restaurant. Restaurant servicescape and service quality are expected to make customers satisfy and create repurchase intention. This study examines the effect of restaurant servicescape and service quality on repurchase intention through customer satisfaction. It addresses three restaurants: A to Z, The Tavern, and Bowery. The respondents are 105 people who had visited one of the restaurants and were divided proportionally between the three restaurants. The questionnaires were distributed via google form and the analytical technique for quantitative data was applied. The results conclude that restaurant servicescape has positive and significant effect on customer satisfaction and similarly service quality also positive and significant effect on customer satisfaction. Customer satisfaction, restaurant servicescape, and service quality individually have positive and significant effect on repurchase intention. Furthermore, customer satisfaction is a mediating variable between restaurant servicescape and repurchase intention as well as service quality and repurchase intention.